Digital Marketing Strategies and Performance of Tour Operators Supply Chain in the Tourism Industry - Mwalukasa, Boniface Emmanuel (International Journal of Business, Economics, and Social Development, 2024)
Digital marketing strategies are vital in enhancing the performance of tour operators’ supply chains within the tourism sector, increasing visitor numbers, sales, and profit, indirectly affecting the economic growth of a community.  The number of international visitors in Tanzania has remained constant at about one million since 2012. This study investigates the effects of digital marketing Strategies on the performance of tour operators' supply chains in Tanzania, guided by the Resource-Based View theory. Employing a convergent parallel mixed-method design, the study includes a sampling frame consisting of 543 tour operators with a sample size of 230 firms. Data collection involved the utilization of both structured questionnaires and interview guides, followed by analysis employing descriptive statistics and Structural Equation Modelling. The findings demonstrate a positive significant relationship between digital marketing strategies and tour operators’ supply chain performance. The results suggest the integration of Artificial Intelligence into the digital marketing strategies mix to facilitate personalized messaging and enhance analytics. Tour operators need to engage skilled information and communication technology experts and institute continuous training initiatives to increase the quality of their websites and social media platforms ensuring visitors receive updated content to capture the attention of visitors. Attentiveness to visitors’ online feedback is crucial for enhancing product and service delivery and tour operators should focus on increasing website traffic. The results are useful to stakeholders in enhancing the promotion of tourism products and services leading to an increasing the number of visitors.